Comparative spatial lipidomics analysis reveals cellular lipid remodelling in different developmental zones of barley roots in response to salinity. (29th November 2019) - Sarabia, Lenin D.; Boughton, Berin A.; Rupasinghe, Thusitha; Callahan, Damien L.; Hill, Camilla B.; Roessner, Ute
Abstract: Salinity‐induced metabolic, ionic, and transcript modifications in plants have routinely been studied using whole plant tissues, which do not provide information on spatial tissue responses. The aim of this study was to assess the changes in the lipid profiles in a spatial manner and to quantify the changes in the elemental composition in roots of seedlings of four barley cultivars before and after a short‐term salt stress. We used a combination of liquid chromatography–tandem mass spectrometry, inductively coupled plasma mass spectrometry, matrix‐assisted laser desorption/ionization mass spectrometry imaging, and reverse transcription – quantitative real time polymerase chain reaction platforms to examine the molecular signatures of lipids, ions, and transcripts in three anatomically different seminal root tissues before and after salt stress. We found significant changes to the levels of major lipid classes including a decrease in the levels of lysoglycerophospholipids, ceramides, and hexosylceramides and an increase in the levels of glycerophospholipids, hydroxylated ceramides, and hexosylceramides. Our results revealed that modifications to lipid and transcript profiles in plant roots in response to a short‐term salt stress may involve recycling of major lipid species, such as phosphatidylcholine, via resynthesis from glycerophosphocholine. Abstract : Accumulation of glycerophosphocholine may be a component in the salt stress response of seminal roots of barley seedlings by acting as an osmolyte and a substrate for phosphatidylcholine resynthesis following a short‐term salt stress.